The Comparison of Breast milk from Mother with Preterm Infant at 4o C Temperature in 0, 24 and 48 Hours on Bacterial Growth - Saputra, Pandit Bagus Tri; Rochmah, Nur; Wiqoyah, Nurul (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Preterm and fullterm breast milk has different leukocyte and bioactive concentration, which affect it's bactericidal activity and storage duration. The preterm breast milk potentially has longer storage duration than fullterm breast milk The research and guideline about the acceptable of storage duration of preterm breast milk at 4o C was limited. The objective of this study was to assess the correlation of storage duration of preterm breast milk preterm baby at 4o C temperature on bacterial growth.Methods: The study design was experimental using pre-post control groups design. We used 9 samples of breast milk which met the inclusion criteria divided into 3 groups. The first, second and third groups was storage in 4o C for 0, 24 and 48 hours respectively before the inoculation to the culture media.Results: After the samples were kept at 4o C temperature for 0, 24 and 48 hours, the mean bacterial colony forming unit for each group were 92 (±SD 112), 79 (±SD 97) and 63 (±SD 73) CFU respectively. Compared to the first group, the second and third group has lower bacterial colony forming unit but no significant differences statistically (P= 0.214 and P=1.39 respectively). Likewise there was no significant bacterial colony forming unit between second and third group (P=0.086).Conclusion: Storage of preterm breast milk in 4o C for 24 and 48 hours show no change in total bacterial colony count (TBCC)..